Seroprevalence of toxoplasmosis in pregnant women of the Marrakech-Safi region, Morocco - Hoummadi, Laila (Afr Health Sci, 2020)
BACKGROUND: Toxoplasmosis is a parasitic infection caused by an intracellular protozoan named Toxoplasma gondii. Its prevalence had been investigated in several studies throughout the world showing that it varied from one country to another. In contrast, few studies had been carried out on this infection across the kingdom of Morocco, hence the objective of this work, which is the determination of Toxoplasma gondii seroprevalence in the region of Marrakech-Safi. METHODS: The serological results of a cohort of 5692 patients were reviewed retrospectively. Those patients had been into different public and private medical laboratories in the region of Marrakech-Safi for a toxoplasmosis serology, requested between the 1(st) January, 2014 and 31(st) December, 2016. According to each laboratory, the techniques adopted for this serology were ELISA (ELFA, MEIA, EIA) and CMIA. RESULTS: The results showed that for pregnant women, the overall seroprevalence in the study region were 28.88%. CONCLUSION: The variation of Toxoplasma gondii seroprevalence is related not only to climatic factors but also to lifestyle, eating habits, socio-economic status and hygiene conditions. In this study, we noticed that in Morocco, as in other countries, pregnant women encounter several difficulties when serologic screening for toxoplasmosis.